2009
DOI: 10.1159/000166277
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Roles for G Protein-Regulated Adenylyl Cyclase Isoforms: Insights from Knockout and Overexpression Studies

Abstract: Cyclic AMP is a universal second messenger, produced by a family of adenylyl cyclase (AC) enzymes. The last three decades have brought a wealth of new information about the regulation of cyclic AMP production by ACs. Nine hormone-sensitive, membrane-bound AC isoforms have been identified in addition to a tenth isoform that lacks membrane spans and more closely resembles the cyanobacterial AC enzymes. New model systems for purifying and characterizing the catalytic domains of AC have led to the crystal structur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
357
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 323 publications
(365 citation statements)
references
References 194 publications
(246 reference statements)
7
357
0
1
Order By: Relevance
“…Early events in T-cell activation require the intracellular accumulation of calcium to activate key signaling pathways. Human T-cells and lymphoid cell lines, including MT-2 and Kit 225 cells, express AC III 3 known to be activated by calcium (55). Similarly, other groups have shown that high avidity TCR engagement inhibits T-cell proliferation by blocking activation of Stat5, Jak1, and Jak3 mediated by IL-2 or IL-4 (25).…”
Section: Discussionmentioning
confidence: 93%
“…Early events in T-cell activation require the intracellular accumulation of calcium to activate key signaling pathways. Human T-cells and lymphoid cell lines, including MT-2 and Kit 225 cells, express AC III 3 known to be activated by calcium (55). Similarly, other groups have shown that high avidity TCR engagement inhibits T-cell proliferation by blocking activation of Stat5, Jak1, and Jak3 mediated by IL-2 or IL-4 (25).…”
Section: Discussionmentioning
confidence: 93%
“…FSK acts independently of receptors to directly activate all adenylyl cyclases (ACs) except AC 9 (21,22). We found that FSK-stimulated Ramp3 expression was inhibited by WT, but not Cox2 KO, CM (Fig.…”
Section: From Rankl-stimulated Wt But Not Cox2 Ko Bmmsmentioning
confidence: 83%
“…RT-PCR analysis and opioid inhibition of cAMP in DRGs suggest the presence of all AC isoforms except AC2 and AC7 (48). Knock-out studies of AC isoforms implicate both AC1 and AC5 in pain pathways.…”
Section: Discussionmentioning
confidence: 95%